PERFORMANCE OF Clarias gariepinus FED NATIONAL INSTITUTE FOR FRESHWATER FISHERIES RESEARCH (NIFFR) FEED SUPPLEMENTED WITH NUTRASE XYLANASE - IBIYO , L. M. O; MOGAJI, O; JOSHUA, F. O. (Nigerian Journal of Fisheries, 2015)
Eight weeks feeding experiment was conducted to evaluate xylanase inclusion into un-extruded and extruded diets of Clarias gariepinus fingerlings in a 2 x 3 factorial design. Triplicated groups of 10 fingerlings with mean weight of 5.3 g ± 0.5 were used at National Institute for Freshwater Fisheries Research, New Bussa, Niger State, Nigeria. There were significant differences (P < 0.05) in final weight, specific growth rate and weight gain of the fish. The fish that fed on the diets produced by cold pelleting supplemented with either yeast or xylanase were not significantly different (P > 0.05) in growth, but were significantly lower than those on diet with enzyme produced by extrusion (P < 0.05). However the groups that fed on diets with xylanase had higher mean weight gain, 20.76 versus 22.39 g fish-1 for yeast and xylanase respectively. There was a reduction in cost per kg of feed with xylanase supplementation compared to yeast as an additive. It was observed that xylanase resulted in better performance which could be due to its effect on the B,1- 4 bonds to expose and reduce the polymers of nutrients that might have been bound up in the cell wall for the available endogenous enzyme. It was concluded that xylanase supplementation in diets of C. gariepinus results in significantly (P < 0.05) higher performance. It will be necessary to carry out further studies on this species.